Development and characterization of sustainable concrete incorporating a high volume of industrial waste materials. (15th February 2023) - Helmy, Sherif H.; Tahwia, Ahmed M.; Mahdy, Mohamed G.; Elrahman, Mohamed Abd
Highlights: The performance of sustainable concrete incorporating high volumes of waste materials was investigated. Compression strength and modulus of elasticity increased when glass powder was involved in the mix. Compression strength improved when rubber tire aggregate was modified using a NaOH solution. Glass and crushed clay brick concrete had lower impact resistance than rubberized concrete at a lower replacement ratio. Natural aggregate was partially or completely replaced by rubber tires, crushed clay brick, and crushed glass aggregates. Abstract: Recycling waste materials instead of using traditional construction materials in civil infrastructure and buildings is a significant step toward reducing greenhouse gas emissions and the consumption of natural resources. The scope of this research is to identify the properties of sustainable concrete where waste materials such as rubber tires, crushed clay bricks, and crushed glass can be utilized to replace the fine or coarse natural aggregate with substitution percentages of 25, 50, and 100 % by volume. Slump, compressive strength, elastic modulus, impact resistance, density, and sorptivity tests were performed. In addition, scanning electron microscopy (SEM) and X–ray diffraction (XRD) were studied to determine the microstructure properties of concrete. The rubberized concrete mixes showed worse workability, while crushed clay brick and crushed glass concrete showed good workability. The decrease in dry density was 55 % less than the control mix when rubber aggregate was used, while it reached 17 % and 4 % when crushed clay brick and crushed glass aggregate were used, respectively. The compression strength and elastic modulus decreased as waste content increased, except for the fine glass mix. The compression strength of the fine glass mixture was 5.58 % greater than that of the control mixture. The sorptivity of sustainable concrete increased when the amount of waste increased, and its value ranged from 2.7 × 10 –3 to 16.5 × 10 –3  mm/s½ compared to the control mix, whose value was 2 × 10 –3  mm/s½. The findings of this investigation demonstrated that the studied waste materials can be used to produce either sustainable lightweight concrete without severe deterioration of mechanical properties or conventional concrete with better mechanical performance.